Estresse crônico melhora a função miocárdica sem alterar a atividade do canal-L para Ca+2 em ratos - Bruder-Nascimento, Thiago [UNESP]; Salome Campos, Dijon Henrique [UNESP]; Leopoldo, Andre Soares; Lima-Leopoldo, Ana Paula; Okoshi, Katashi [UNESP]; Cordellini, Sandra [UNESP]; Cicogna, Antonio Carlos [UNESP] (Arquivos Brasileiros Cardiologia, 2012)
Background: Chronic stress is associated with cardiac remodeling; however the mechanisms have yet to be clarified.Objective: The purpose of this study was test the hypothesis that chronic stress promotes cardiac dysfunction associated to L-type calcium Ca2+ channel activity depression.Methods: Thirty-day-old male Wistar rats (70 - 100 g) were distributed into two groups: control (C) and chronic stress (St). The stress was consistently maintained at immobilization during 15 weeks, 5 times per week, 1h per day. The cardiac function was evaluated by left ventricular performance through echocardiography and by ventricular isolated papillary muscle. The myocardial papillary muscle activity was assessed at baseline conditions and with inotropic maneuvers such as: post-rest contraction and increases in extracellular Ca2+ concentration, in presence or absence of specific blockers L-type calcium channels.Results: The stress was characterized for adrenal glands hypertrophy, increase of systemic corticosterone level and arterial hypertension. The chronic stress provided left ventricular hypertrophy. The left ventricular and baseline myocardial function did not change with chronic stress. However, it improved the response of the papillary muscle in relation to positive inotropic stimulation. This function improvement was not associated with the L-type Ca2+ channel.Conclusion: Chronic stress produced cardiac hypertrophy; however, in the study of papillary muscle, the positive inotropic maneuvers potentiated cardiac function in stressed rats, without involvement of L-type Ca2+ channel. Thus, the responsible mechanisms remain unclear with respect to Ca2+ influx alterations. (Arq Bras Cardiol 2012;99(4):907-914)
Chronic Stress Improves the Myocardial Function without Altering L-type Ca+2 Channel Activity in Rats
Keywords: Stress, physiological / complications; stress, physiological / physiopathology; cardiovascular diseases / psychology; rats; papillary muscles